Distinct plasmablast developmental intermediates produce graded expression of IgM secretory transcripts - Evelyn P. Sievert; Marissa C. Franke; Kayla B. Thomas; Yoseop Yoon; Yongsheng Shi; Roger Sciammas (Cell Reports)
Summary: Differentiation into plasma cells (PCs) enables secretion of ∼10,000 immunoglobulin molecules per second. This extraordinary capacity requires the upregulation of PC transcriptional determinants that specify PC fate, increase immunoglobulin mRNA synthesis, coordinate alternative 3′ end processing of the heavy chain transcript from the distal to proximal polyadenylation site (PAS), and remodel the secretory pathway. We developed a dual-fluorescent protein reporter mouse to prospectively study the post-transcriptional-level transition from membrane anchored to secretory immunoglobulin M; μM-PAS and μS-PAS, respectively. We observed (1) graded μS-PAS usage during PC differentiation, (2) IRF4 and Blimp-1 functioned hierarchically to increase μ abundance as well as μS-PAS usage, and (3) graded μS populations did or did not express Blimp-1. Interestingly, the low and high μS and Blimp-1-expressing populations arose from distinct developmental intermediates that exhibited dissimilar endoplasmic reticulum features. The distinct cell and μS-PAS fate trajectories may have implications for derivatization of the secretory pathway.